2023
DOI: 10.1186/s12889-023-15798-2
|View full text |Cite
|
Sign up to set email alerts
|

What difference does it make? A laboratory experiment on the effectiveness of health-oriented leadership working on-site compared to the digital working context

Abstract: Background Health-oriented leadership (HoL) represents an important workplace resource for employees. However, as opportunities to work from home increase, the question arises, whether leadership is more or less effective in digital working contexts compared to working on-site. Methods The current research investigates, whether the effectiveness of health-oriented leadership in terms of staff care is influenced by the working context. In a laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Overall, according to current research, initial quantitative studies demonstrated the effectiveness of StaffCare also for digital, remote work contexts during the COVID-19 pandemic [ 9 , 19 – 21 ]. Three of these studies analyzed StaffCare in comparison between office and home office [ 9 , 20 , 21 ]. Their findings indicated i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, according to current research, initial quantitative studies demonstrated the effectiveness of StaffCare also for digital, remote work contexts during the COVID-19 pandemic [ 9 , 19 – 21 ]. Three of these studies analyzed StaffCare in comparison between office and home office [ 9 , 20 , 21 ]. Their findings indicated i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings indicated i.e. positive effects of StaffCare on employees’ well-being [ 20 ] as well as negative effects on employees’ mental exhaustion [ 21 ] and psychosomatic complaints [ 20 ] in both work contexts whereas two studies found lower effectiveness of StaffCare on employees’ engagement and job satisfaction in home office in comparison to office [ 9 , 21 ]. Furthermore, two other studies conducted during the COVID-19 pandemic showed that, one, telework-oriented leadership (including StaffCare) affected teleworkers’ happiness well-being via strain by ensuring communication and information exchanges between teleworkers [ 60 ] and, two, that the positive relationship between StaffCare and follower health was stronger in times of crisis [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation